2017
DOI: 10.1155/2017/6865789
|View full text |Cite
|
Sign up to set email alerts
|

TLR Specific Immune Responses against Helminth Infections

Abstract: Despite marked improvement in the quality of lives across the globe, more than 2 million individuals in socioeconomically disadvantaged environments remain infected by helminth (worm) parasites. Owing to the longevity of the worms and paucity of immunologic controls, these parasites survive for long periods within the bloodstream, lymphatics, and gastrointestinal tract resulting in pathologic conditions such as anemia, cirrhosis, and lymphatic filariasis. Despite infection, an asymptomatic state may be maintai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 106 publications
0
16
0
Order By: Relevance
“…The role for antibody-dependent cell-mediated cytotoxicity 46 , 66 , 67 and the TLR4 pathway in immunity to onchocerciasis has also been documented 31 . The potential role of TLR in mediating interactions between helminth parasites and the host immune system has been described 68 . Many filarial parasites (including O. volvulus ) indeed harbour a Wolbachia endosymbiont which can interact with the innate immune system through TLR2 and TLR4 69 .…”
Section: Discussionmentioning
confidence: 99%
“…The role for antibody-dependent cell-mediated cytotoxicity 46 , 66 , 67 and the TLR4 pathway in immunity to onchocerciasis has also been documented 31 . The potential role of TLR in mediating interactions between helminth parasites and the host immune system has been described 68 . Many filarial parasites (including O. volvulus ) indeed harbour a Wolbachia endosymbiont which can interact with the innate immune system through TLR2 and TLR4 69 .…”
Section: Discussionmentioning
confidence: 99%
“…The vital function of antibody-dependent cell-mediated cytotoxicity (ADCC) [ 50 , 81 , 82 ] has also been reported and research on the candidates planned for clinical trials, Ov-RAL-2 and Ov103, reported that ADCC is a crucial mechanism for a successful prophylactic vaccine against this infection [ 83 ]. The importance of TLRs in mediating interactions between helminthic parasites and the human host immune system has also been described [ 84 ] and the TLR4 pathway has been implicated in host immunity to onchocerciasis [ 38 ]. The endosymbiont Wolbachia, present in many filarial parasites (including O. volvulus ) possesses a major surface protein which interacts with the innate immune system through TLR2 and TLR4 leading to an inflammatory response characterized by proinflammatory cytokine expression in murine dendritic cells and macrophages [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between TLRs and filarial nematode has gained special attention because these complex interactions are important for determining the immunological outcome of the disease 18 . During acute phase of filarial infection, TLR‐mediated pro‐inflammatory activation of DCs promotes Th1‐type inflammatory responses 45 …”
Section: Outcome Of the Toll‐like Receptors (Tlrs) On Dcs And Filariamentioning
confidence: 99%
“…Studies have revealed that the host immune cells are mostly activated by interacting with the Toll‐like receptors (TLRs) present on the surfaces of the APCs 17 . Since the last few decades, the therapeutic potentials of these TLRs are widely accepted in case of various parasitic infections 18 . Recently, a parasite‐derived molecule known as filarial sheath antigen (FSAg) has been reported to interact with the TLR4 on host DCs 14‐16,19 …”
Section: Introductionmentioning
confidence: 99%